Penerapan Algoritma Apriori pada Pengolahan Data Transaksi Penjualan di Minimarket Priyo Kota Lubuklinggau - Andri Anto Tri Susilo (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2018)
The development of mini-market in 2017 is extraordinary. If you ever heard the price of goods and many retail items. A most bona fide survey company, there is a change of shopping pattern from supermarket to minimarket, Dilubuklinggau, minimarket which can be classified into 2 that is minimarket owned by big company and minimarket owned by individual. In the process of data processing sales of goods, all minimarkets in Lubuklinggau City already using a database-based system. Ongoing sales transactions every time can lead to data collection, analysis used to generate information or information relevant to the minimarket. In addition, using this technique can also find patterns of products that are often used. To generate rules or rules between specific items for products that are technically used technical rules to find relationships between relations or items between sets. The end result of this study is the formation of several joint patterns of products sold that can be used by minimarket owners in the list of goods sold.